Stability of Optical and Mechanical Properties in Multi-Shade, Group-Shade, and Single-Shade Resin Composites - Violina Gunawan; Joanne Jung Eun Choi (International Journal of Dentistry, 2025)
Conclusions: SS RC shows the best stability in both optical and mechanical properties, whereas GS RC exhibits variable performance with no trend requiring further investigations. The MS RC shows the least color and translucency stability but highest hardness throughout the experiment.